Characterization Of Halogen-Free Core Material With Various Flame Retardants - Lim, Patrick Wye Kheong (2012)
The effect of three different types of halogen-free flame retardants, which are the intumescent ammonium polyphosphates (APP), melamine cyanurate (MC) and calcium borate (CaB) on epoxy/glass fiber composites was studied. The single and hybrid flame retardant fillers were used to investigate the composites fire properties, mechanical and thermal properties. In general, after decompose at 700oC, CaB leaves behind the highest residual content, which mainly comprises of chars and glassy substrates. This is followed by APP which decomposes and forms the chars, while MC decomposes mainly into volatile gases. Among the three types, APP performed the best in flame retardancy while CaB is not effective in this composite.